2020
DOI: 10.1167/tvst.9.2.40
|View full text |Cite
|
Sign up to set email alerts
|

Cone Identification in Choroideremia: Repeatability, Reliability, and Automation Through Use of a Convolutional Neural Network

Abstract: Adaptive optics imaging has enabled the visualization of photoreceptors both in health and disease. However, there remains a need for automated accurate cone photoreceptor identification in images of disease. Here, we apply an open-source convolutional neural network (CNN) to automatically identify cones in images of choroideremia (CHM). We further compare the results to the repeatability and reliability of manual cone identifications in CHM. Methods: We used split-detection adaptive optics scanning laser opht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In the present study, our results from the centrally retained retinal area showed significantly lower cone density in CHM subjects compared to normal-sighted controls at 1°, 2°, and 4° temporal from the fovea, as well as larger intercone spaces. These findings are consistent with other recent publications on parafoveal cone density in CHM which have found decreased cone density and heterogeneous cell morphology 8 , 12 , 21 , 22 , 36 Abnormal cone coverage and increased spacing in CHM compared to controls have also been reported in previous studies. 21 , 50 , 51…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, our results from the centrally retained retinal area showed significantly lower cone density in CHM subjects compared to normal-sighted controls at 1°, 2°, and 4° temporal from the fovea, as well as larger intercone spaces. These findings are consistent with other recent publications on parafoveal cone density in CHM which have found decreased cone density and heterogeneous cell morphology 8 , 12 , 21 , 22 , 36 Abnormal cone coverage and increased spacing in CHM compared to controls have also been reported in previous studies. 21 , 50 , 51…”
Section: Discussionsupporting
confidence: 93%
“…Intergrader agreement for cone identifications in CHM is high; however, differences do occur. 22 , 34 When reviewer PX disagreed on a cone selection made by JIWM (either a false positive or a false negative), the segmentation was performed according to PX's discretion, with the location of the cone recorded. Investigators JIWM and PX then reviewed jointly all segmentations to come to agreement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One grader (J.I.W.M.) manually identified cones in all ROIs using custom software . The grader was masked to injected vs control eye and time point for each study participant and was able to adjust the brightness and contrast of the image while selecting cones.…”
Section: Methodsmentioning
confidence: 99%
“…manually identified cones in all ROIs using custom software. 47 The grader was masked to injected vs control eye and time point for each study participant and was able to adjust the brightness and contrast of the image while selecting cones. Cone centers were used to determine Voronoi boundaries and bound cone density was calculated for each ROI.…”
Section: Cone Density Measurementsmentioning
confidence: 99%